Expectations of Parents of Children with Disabilities in Bhutan Inclusive Schools. (16th April 2023) - Jigyel, Karma; Miller, Judith; Mavropoulou, Sofia; Berman, Jeanette
ABSTRACT: The purpose of this study was to investigate parents' expectations of including their children with disability in three pilot inclusive education schools located in urban, semi-urban, and rural regions in Bhutan. The participants in this study included 26 parents (13 fathers and 13 mothers) of children with disability in either full or partial inclusion programs. Parent interviews were transcribed and analysed using both manual thematic analysis and text mining software (Leximancer). Results revealed parents' expectations for schools were to have teachers trained to teach children with disabilities and provide appropriate adaptations of physical facilities. Parents also expected improvement in social skills and an independent future for their children. The findings have implications for the policymakers and schools when delivering services to children with disability and their parents.